2009
DOI: 10.1590/s0104-66322009000200002
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the hydrolysis of gamma irradiated lignocelluloses

Abstract: -The effect of high-dose irradiation as a pretreatment method on two common lignocellulosic materials; hardwood (Khaya senegalensis) and softwood (Triplochiton scleroxylon) were investigated by assessing the potential of cellulase enzyme derived from Aspergillus flavus Linn isolate NSPR 101 to hydrolyse the materials. The irradiation strongly affected the materials, causing the enzymatic hydrolysis to increase by more than 3 fold. Maximum digestibility occurred in softwood at 40kGy dosage of irradiation, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…A comparison on gamma ray irradiation pretreatment on soft and hardwood has also been carried out using different level of dosage ranges between 10-100 kGy [37]. The study found that the most suitable condition for softwood was at 40 kGy, while higher dosage is required to pretreat hardwood (90 kGy).…”
Section: Gamma-ray Irradiationmentioning
confidence: 99%
“…A comparison on gamma ray irradiation pretreatment on soft and hardwood has also been carried out using different level of dosage ranges between 10-100 kGy [37]. The study found that the most suitable condition for softwood was at 40 kGy, while higher dosage is required to pretreat hardwood (90 kGy).…”
Section: Gamma-ray Irradiationmentioning
confidence: 99%
“…Starch and cellulosic and pectic polysaccharides are degraded by cleavage of glycosidic bonds [ 13 ]. High doses of gamma rays depolymerize or delignify the cell wall constituents [ 15 , 16 ]. Loss in the fiber content has been observed in plant matter [ 17 ].…”
Section: Gamma Irradiationmentioning
confidence: 99%
“…A reduction in the rumen dry matter has been found in spruce sawdust, barks of spruce, pine, and larch when irradiated with high doses of gamma rays due to the solubilization and partial breakdown of the dry matter [ 18 ]. The degradation of cell wall has been reported to show increase in digestibility of the organic matter [ 16 ] as evidenced in rice straw [ 19 ], barley straw, pea straw, sugarcane bagasse, sunflower hulls, and pine sawdust [ 20 ]. Combined NaOH and gamma radiation treatment of wheat straw, cotton shells, peanut and soybean shells, and extracted olive oil cake and extracted unpeeled sunflower seeds showed improved digestibility compared to the individual methods [ 21 ].…”
Section: Gamma Irradiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Gamma radiation and electron beam irradiation pretreatment have been used to improve enzymatic digestibility solely or in combination with alkali agent [31,[320][321][322][323]. However, the enzymatic efficiency of irradiation-pretreated biomass is typically still low, presumably due to the introduction of insoluble crosslinkages.…”
Section: Irradiation Pretreatmentmentioning
confidence: 99%